Biosorption of Ni(II) using alkaline-treated rice husk / Insyirah Mohamad Shah - Insyirah , Mohamad Shah (2017)
Rice husk has been widely reported as a good sorbent for heavy metals. Alkaline-treated rice husk were used to investigate the potential of Ni(II) adsorption from synthetic solutions and wastewater in batch systems. Effects of operational variables such as pH, contact time, adsorbent dose, initial Ni(II) concentration were studied. Optimum Ni(II) adsorption was observed at pH 6. Experimental data showed increased amount of adsorbed Ni(II) with increasing adsorbent dose and decreased percent of adsorption with increasing initial Ni(II) concentration. The adsorption became constant after 40 min into the experiment. Biosorption mechanism of rice husk was analyzed using SEM, FTIR. ICP-OES and XRD. Langmuir adsorption isotherm was also studied to determine the respective constants and showed that the adsorption was favorable and the KL was 0.292 L/mg. Results revealed that natural base could be used as efficient as synthetic bases for Ni(II) removal from wastewaters. Ni uptake from wastewater was not reduced to the parameter limit of effluent by the Environmental Quality (Industrial Effluent) Regulations 2009.